ChemInform Abstract: Sustainable Synthesis of Diverse Privileged Heterocycles by Palladium‐Catalyzed Aerobic Oxidative Isocyanide Insertion. Issue 21 (2nd May 2013) - Vlaar, Tjoestil; Cioc, Razvan C.; Mampuys, Pieter; Maes, Bert U. W.; Orru, Romano V. A.; Ruijter, Eelco
Abstract The novel and scalable title synthesis of a wide variety of pharmaceutically relevant heterocyclic systems, which is demonstrated for the intermediate (XXII) of astemizole and norastemizole, is presented by using an easily handled and relatively low‐cost catalyst.